DAMPAK DESENTRALISASI FISKAL TERHADAP KINERJA FISKAL DAERAH DAN KETAHANAN PANGAN DI WILAYAH PROVINSI JAWA BARAT - Rindayati, Wiwiek; Sanim, Bunasor; Hutagaol, M Parulian; Siregar, Hermanto (Jurnal Manajemen dan Agribisnis, 2011)
The implementation of fiscal decentralization in accordance with Law No 32/2004 regarding local government and No. 33/2004 regarding inter-government fiscal relationship was considered as the new  era management  and local goverment budgets. The objectives of this study are (1) to analyze factors affecting regional fiscal performance, regional economy performance, poverty ond food security performance, (2) to evaluate impact of fiscal decentralization policy on poverty and food security in West Java.The descriptive analysis and simultaneous econometrical models were used in this study, using pooled time series data of  1995-2005 and cross section data of 13 kabupaten estimated using the 2SLS method. The result of the study shows that the DAU was the source of 68 persen of regional income.The routine expenditures were the largest regional expenditures (77 persen). The policy of increasing wages of agricultural has affectively increased food security and  poverty alleviation in West Java.